Review of The Special Operations Executive in Malaya: World War II and the Path to Independence, by Rebecca Kenneison - Kankan Xie (Journal of British Studies, 2020)
The past few years have seen a growing number of scholarly works on British operations in Southeast Asia and their relationships with local resistance in World War II. Particularly intriguing is the mysterious last-minute deal struck between the British in Malaya and the Chinese-dominated Malayan Communist Party, or MCP, before the Japanese takeover...